Investigating cognitive ability and self-reported driving performance of post-stroke adults in a driving simulator - Blane, Alison; Falkmer, Torbjorn; Lee, Hoe; Dukic Willstrand, T. (Thomas Land Publishers, 2018)
Background: Safe driving is a complex activity that requires calibration. This means the driver can accurately assess the level of task demand required for task completion and can accurately evaluate their driving capability. There is much debate on the calibration ability of post-stroke drivers. Objectives: The aim of this study was to assess the cognition, self-rated performance, and estimation of task demand in a driving simulator with post-stroke drivers and controls. Methods: A between-groups study design was employed, which included a post-stroke driver group and a group of similarly aged older control drivers. Both groups were observed driving in two simulator-based driving scenarios and asked to complete the NASA Task Load Index (TLX) to assess their perceived task demand and self-rate their driving performance. Participants also completed a battery of psychometric tasks to assess attention and executive function, which was used to determine whether post-stroke cognitive impairment impacted on calibration. Results: There was no difference in the amount of perceived task demand required to complete the driving task. Despite impairments in cognition, the post-stroke drivers were not more likely to over-estimate their driving abilities than controls. On average, the post-stroke drivers self-rated themselves more poorly than the controls and this rating was related to cognitive ability. Conclusion: This study suggests that post-stroke drivers may be aware of their deficits and adjust their driving behavior. Furthermore, using self-performance measures alongside a driving simulator and cognitive assessments may provide complementary fitness-to-drive assessments, as well as rehabilitation tools during post-stroke recovery.